Improved GaLV-TR Glycoproteins to Pseudotype Lentiviral Vectors: Impact of Viral Protease Activity in the Production of LV Pseudotypes - Tomás, Hélio A. (Mol Ther Methods Clin Dev, 2019)
Lentiviral vectors (LVs) are excellent tools for gene transfer into mammalian cells. It is noteworthy that the first gene therapy treatment using LVs was approved for commercialization in 2017. The G glycoprotein from rhabdovirus vesicular stomatitis virus (VSV-G) is the glycoprotein most used to pseudotype LVs, due to its high efficiency in transducing several cell types and its resistance to viral vector purification and storage conditions. However, VSV-G expression induces cytotoxicity, which limits LV production to short periods. As alternative to VSV-G, γ-retrovirus glycoproteins (4070A derived, GaLV derived, and RD114 derived) have been used to pseudotype both γ-retroviral vectors (RVs) and LVs. These glycoproteins do not induce cytotoxicity, allowing the development of stable LV producer cells. Additionally, these LV pseudotypes present higher transduction efficiencies of hematopoietic stem cells when compared to VSV-G. Here, new 4070A-, RD114-TR-, and GaLV-TR-derived glycoproteins were developed with the aim of improving its cytoplasmic tail R-peptide cleavage and thus increase LV infectious titers. The new glycoproteins were tested in transient LV production using the wild-type or the less active T26S HIV-1 protease. The GaLV-TR-derived glycoproteins were able to overcome titer differences observed between LV production using wild-type and T26S protease. Additionally, these glycoproteins were even able to increase LV titers, evidencing its potential as an alternative glycoprotein to pseudotype LVs.